The peculiarities of medical discourse in medical practice of doctor-pathologist. - Tatsenko, N. V.; Moskalenko, R. A.; Perelomova, O. S.; Kondratyuk, O. S.; Bezuglyi, M. A. (Морфологія / Morphologia / Morfologìâ, 2012)
The paper is devoted to the peculiarities of medical pathoanatomical discourse as coherent speech and as linguistic correlate of medical practice taking into account the analysis of its strategies and tactics. The purpose of the paper is to provide a multifaceted analysis of the speech strategies and tactics of pathoanatomical discourse and ways of their implementation. The main strategies of the pathoanatomical variant of medical discourse are anticipating strategy, diagnosing strategy and explaining one.The supporting strategies are pragmatic, interactive and rhetorical one. The pragmatic strategy is implemented through contact establishing tactics, the interactive one – with the help of control tactics, the rhetoric one – with the help of attention correction tactics.The above mentioned tactics and strategies are used in the distinguishing of major, closely interrelated strategies: "contact strategy" (to establish contact with patient’s relatives - phatic replicasof greeting and addressing) and the "strategy of explanation" (used in the practice ofpathologist for a detailed explanation of the reasons of patient’s death). The ethic aspect of speech conduct of doctor-pathologist is analyzed.